USE OF COMPUTER ANALYSIS OF OCCLUSAL CONTACTS IN ORTHOPEDIC PATIENTS WITH SECONDARY DEFORMITIES OF DENTITION (LITERATURE REVIEW) - O.V. Fedorova (Український стоматологічний альманах)
In patients with orthopedic secondary deformations of dentition (SDD) is often needed to change the shape of crowns of teeth, the ratio of dentition and jaws. Optimal occlusion ratio is important for the quality restoration of dentition. To improve the results of orthopedic treatment of patients with SDD it is necessary to control occlusal relationships at all stages of treatment, and the results should be stored, compared and analyzed. Studying the issues of diagnosis and treatment of patients with secondary deformities of dentition (SDD) we met the need to study the occlusal relationships. Modern stomatology uses different methods to research interocclusal correlations of teeth and jaws. For long time the main material for determining occlusal relationships was the articulation of a paper. Now This method is the most commonly used, but significant drawback of this method is the inability to record and store the data, biometric study of occlusal contacts, so far modern researchers recommend qualitative assessment of the value of the jaws to other methods of occlusal analysis.